Sosialisasi Pencegahan dan Pengendalian Penyakit Tidak Menular - Sari, Mega Puspa; Hamal, Dian Kholika; Mulyawati, Devi Annisa; Unais, Junaijah Ummu; Pratiwi, Teti (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2024)
Background: The increase in the prevalence of non-communicable diseases has become a serious threat, especially in the development of public health. Non-Communicable Diseases (NCD) in Indonesia are predicted to experience a significant increase in 2030. Its chronic nature and attacking productive age, causes NCDs to not only be a health problem, but also affect the resilience of the national economy if not controlled properly, correctly and continuously. The purpose of this community service is to increase public knowledge and awareness in preventing and controlling non-communicable diseases such as hypertension, stroke, heart disease and diabetes mellitus. Method: This activity is in the form of providing counseling in the Rawa Buntu Village Hall regarding non-communicable diseases & their prevention, PTM Nutrition, BMI counting (body mass index) exercises, and blood pressure checks to determine hypertension status and early detection of participants. Results: The results of blood pressure measurements showed that 25% had hypertension. While the BMI category is 41% with obesity BMI status and 22% with overweight BMI status. The mean posttest and pretest scores showed an increase in students' understanding of the prevention and control of non-communicable diseases after being given counseling or material explanations. Conclusion: One of the effective and efficient PTM controls is empowering and increasing community participation. Therefore, one way to reduce the prevalence of NCDs is to make individuals and families aware of reducing the prevalence rate, there is a need for further education at least at the family level regarding non-communicable diseases.